INVENTARISASI KEANEKARAGAMAN JAMUR MAKROSKOPIS DI GUNUNG BETUNG PESAWARAN - Yeni Afrestia; Agil Lepiyanto; Triana Asih (EDUBIOLOCK, 2023)
This study aims to (1) determine the macroscopic fungal species found on Mount Betung Pesawaran and (2) determine the diversity index of the macroscopic fungi found on Mount Betung Pesawaran. (3) knowing the benefits of research results in the form of encyclopedia learning resources. The research was conducted with a qualitative approach, the research used was descriptive. The sampling technique of macroscopic mushrooms was carried out using the roaming method (exploration), the quadratic method, and purposive sampling. The results of macroscopic mushroom research conducted at Gunung Betung Pesawaran found 4 orders with 19 species, the orders found were the order Auriculariales (Auricularia auricular), the order Polyporales (Trametes pubescens, Trichaptum abietinum, Earliella scabrosa, Ganoderma boninense, Trametes gibbosa, Ganoderma aplanatum, Pycnoporus cinnabarinus, Ganoderma lucidium, Polyporus arcularius) of the order Agaricales (Sarcoscypha coccinea, Marasmius siccus, Coprinellus disseminates, Gymnopilus luteofolius, Oudemansiella mucida, Xylaria polymorpha, Schizophyllum commune, Clitocybe nebularis) and the order Russulales (Stereum hirsutum).